2021
DOI: 10.1523/jneurosci.1141-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Does the Prefrontal Cortex Play an Essential Role in Consciousness? Insights from Intracranial Electrical Stimulation of the Human Brain

Abstract: A central debate in philosophy and neuroscience pertains to whether PFC activity plays an essential role in the neural basis of consciousness. Neuroimaging and electrophysiology studies have revealed that the contents of conscious perceptual experience can be successfully decoded from PFC activity, but these findings might be confounded by postperceptual cognitive processes, such as thinking, reasoning, and decision-making, that are not necessary for consciousness. To clarify the involvement of the PFC in cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 139 publications
4
50
0
Order By: Relevance
“…While negative results should be treated with caution, it is interesting that a recent review of massive stimulation study failed to find evidence for specific perceptual modulations following frontal lobe stimulations ( Raccah et al. 2021 ) again in agreement with converging evidence from functional specialization and cortical lesion data.…”
Section: Three Criteria For Identifying Candidates For Conscious Contentmentioning
confidence: 66%
“…While negative results should be treated with caution, it is interesting that a recent review of massive stimulation study failed to find evidence for specific perceptual modulations following frontal lobe stimulations ( Raccah et al. 2021 ) again in agreement with converging evidence from functional specialization and cortical lesion data.…”
Section: Three Criteria For Identifying Candidates For Conscious Contentmentioning
confidence: 66%
“…Collectively, our results are aligned with the theoretical framework of global neuronal workspace theory, which attempts to describe the neurocognitive mechanisms of conscious access ( Dehaene et al, 1998 ; Dehaene and Changeux, 2011 ; Mashour et al, 2020 ). Access consciousness refers to the broad cognitive availability of sensory information, which often is measured based on report or task performance (as in this study), and is distinct from phenomenal consciousness, which has been defined as experience itself and hypothesized to be independent of post-perceptual processing in anterior cortex ( Block, 2005 ; Raccah et al, 2021 ). According to workspace theory, a reverberant network that includes both prefrontal and posterior parietal cortex serves to sustain, amplify, and make available neural representations, with a ‘broadcasting’ effect that allows access by otherwise non-conscious cognitive processors ( Mashour et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these subcortical regions send projections to cortex (Briand et al, 2007;Hoover and Vertes, 2007) but there is limited evidence of a direct role of cortical areas in regulating behavioral arousal. The cortical mechanisms of consciousness have been a subject of recent debate, with specific controversy as to whether the prefrontal cortex plays a causal role (Boly et al, 2017;Odegaard et al, 2017;Raccah et al, 2021). We recently demonstrated that cholinergic stimulation of prefrontal cortex-via local carbachol delivery-in anesthetized rats induced wakefulness despite the continued presence of sevoflurane anesthesia (Pal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%